Seroid E-Module on Electrical Material on Learning Outcomes of Class VI Elementary School Students - Azizah; Melyani Sari Sitepu; Karmila (Universitas Pendidikan Ganesha, 2023)
The available learning media still need to be improved and still limited in the learning process, especially in science subjects, because they only use textbooks and occasionally do simple practices. This study aimed to prove the effectiveness of the Serli E-Module based on Android (Seroid E-Module) on electricity subject to the learning outcomes of sixth-grade elementary school students. This research is conducted in two groups: the experimental group and the control group. The research design used in this study was the control group pre-test and post-test design. The subjects in this study were 35 students of sixth-grade elementary school. The instrument used is a test instrument, namely multiple choice questions tested for validity and reliability. Data analysis used the conditional test, namely the normality and homogeneity tests, and hypothesis testing using the paired sample t-test assisted by SPSS For Windows 25. The results of this study show that the use of Seroid E-Modules in electricity material is effectively used on student learning outcomes. So, it can be concluded that the Seroid E-Module on electricity material can be used to improve the learning outcomes of class VI elementary school students.